Microeconomic Analysis of Selected Aspects of the First Mission of Public Universities Operating in the Czech Republic - Tetřevová Liběna; Vlčková Vladimíra (STEF92 Technology Ltd., 2016)
This paper pays attention to selected aspects of the first mission of public universities operating in the Czech Republic. The authors of the paper aim to analyze the structure of the faculties of public universities operating in the Czech Republic from the point of view of their field of study, and also to analyze and evaluate the structure of students and academic staff of these faculties both from the point of view of the faculty field of study, and from the point of view of their mutual relationships.
Mikroekonomická analýza vybraných aspektů prvního poslání veřejných univerzit působících v České republice
Keywords: higher education institutions; public university; faculty; first mission; education; vysokoškolské instituce; veřejná univerzita; fakulta; první poslání; vzdělávání